The Impact of the Institutional Innovations Introduced by the Treaty of Lisbon on the European Union's External Action - Gheorghe Ciascai (CES Working Papers, 2011)
The Treaty of Lisbon has brought major innovations in the institutional framework of the EU. The purpose of this paper is to highlight the possible consequences of these institutional innovations on the management and the implementation of the European Union's external action, particularly in the field of Common Foreign and Security Policy (CFSP).
Keywords: 330; Treaty of Lisbon; EU's external action; Common Foreign and Security Policy; European Service of External Action Romania